144k views
0 votes
Solve the equation 9k2 – 6k = 11 by completing the square.

User Thames
by
5.3k points

2 Answers

5 votes

The answer to 9k2 – 6k = 11 is k = 11/12. Though, I'm not sure by the square part.

Here's the decimal form: k=0.91667

Steps:

Multiply the numbers. (9*2)

Add similar elements. (18k - 6k = 11)

Divide both sides by 12.

Simplify.

-

Hope this helped!

User MMALSELEK
by
5.8k points
6 votes

Answer:

The solutions of the given equation are
k=(1)/(3)+(2)/(√(3)) and
k=(1)/(3)-(2)/(√(3)).

Step-by-step explanation:

The given equation is


9k^2-6k=11

Divide both sides by 9.


k^2-(2)/(3)k=(11)/(9)

If an expression is
x^2+bx then we need to add
((b)/(2))^2 in the expression to make it perfect square.

In the above equation
b=(2)/(3), so add
((1)/(3))^2 on both the sides.


k^2-(2)/(3)k+((1)/(3))^2=(11)/(9)+((1)/(3))^2


(k-(1)/(3))^2=(11)/(9)+(1)/(9)


(k-(1)/(3))^2=(12)/(9)


(k-(1)/(3))^2=(4)/(3)

Taking square root both the sides.


k-(1)/(3)=\pm \sqrt{(4)/(3)}

Add 1/3 on both the sides.


k=(1)/(3)\pm (2)/(√(3))

Therefore the solutions of the given equation are
k=(1)/(3)+(2)/(√(3)) and
k=(1)/(3)-(2)/(√(3)).

User Linker
by
5.5k points